2014
DOI: 10.11604/pamj.2014.17.133.3370
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of lymphatic filariasis in Ghana, explained by the possible existence of two strains of Wuchereria bancrofti

Abstract: IntroductionLymphatic filariasis is a debilitating disease caused by the filarial worm Wuchereria bancrofti. It is earmarked for elimination by the year 2020 through the Global Program for the Elimination of LF (GPELF). In Ghana, mass treatment has been on-going since the year 2000. Earlier studies have revealed differing epidemiology of LF in the North and South of Ghana. This study was therefore aimed at understanding the possible impacts of W. bancrofti diversity on the epidemiology and control of LF in Gha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The northern regions of the country exhibit higher prevalence compared to the southern regions, but the middle forest belt is relatively free from the infection (Gyapong, Adjei andSackey, 1996: Dunyo et al, 1996). Elsewhere, a study has revealed some level of genetic variability in parasites strains in the two endemic areas (de Souza et al, 2014). In addition, Pi-Bansa et al, (2019), identi ed a vector of very high vectorial capacity speci c to the coastal areas i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The northern regions of the country exhibit higher prevalence compared to the southern regions, but the middle forest belt is relatively free from the infection (Gyapong, Adjei andSackey, 1996: Dunyo et al, 1996). Elsewhere, a study has revealed some level of genetic variability in parasites strains in the two endemic areas (de Souza et al, 2014). In addition, Pi-Bansa et al, (2019), identi ed a vector of very high vectorial capacity speci c to the coastal areas i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphatic filariasis (LF), the arthropod-borne disease, is a significant public health problem in most developing countries [1]. The disease affects more than 120 million people worldwide and is transmitted by thread-like nematode parasites including Wuchereria bancrofti which accounts for 90% of the infection [2].…”
Section: Introductionmentioning
confidence: 99%
“…The TMs investigated in the study were obtained from members of the Ghana Federation of Traditional Medicines Practitioners Association (GHAFTRAM), following an interaction and administration of a questionnaire. A total of 15 TMs used for the treatment of schistosomiasis (7), onchocerciasis (6) and LF (2) were collected (Table 1). Formulations comprised between one to five plant species and were available in two forms: aqueous herbal preparations and dried powdered herbs.…”
Section: Traditional Medicinesmentioning
confidence: 99%
“…Endemic neglected tropical diseases (NTDs) in Ghana include schistosomiasis (SCH), onchocerciasis (ONCHO) and lymphatic filariasis (LF) [1][2][3][4][5][6][7]. SCH is caused by the blood flukes Schistosoma haematobium which is responsible for the highly prevalent urinary schistosomiasis, and S. mansoni, which causes intestinal schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%